PENGARUH PENDEKATAN BELAJAR TERHADAP KELULUSAN OSCE UKMPPD MAHASISWA FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2020)
ABSTRACT Learning strategies or commonly known as learning approaches are the intentions and motivations of individuals and the use of appropriate strategies when dealing with the learning environment. In general, learning strategies can be divided into two categories, namely a deep approach and a surface approach. A deep approach is characterized by a desire to understand the material so as to produce good quality learning outcomes. A student who uses an in-depth approach has the intention to understand learning material and is motivated by an interest in learning material. Conversely, a surface approach is characterized by a desire to achieve minimal results with minimal effort resulting in low quality learning outcomes. The superficial approach is related to various forms of rote learning, with fear of failure as the dominant motivation. Therefore, the learning approach can influence learning outcomes. One of the learning outcomes assessed is the Objective Structured Clinical Examination (OSCE) Student Competency Test for Doctor Professional Programs (UKMPPD). The purpose of this study is to look at the effect of the learning strategies and OSCE UKMPPD graduation period of May 2018 and August 2018 in medical profession students of the Faculty of Medicine and Health Sciences University of Jambi (FKIK UNJA). The research method is descriptive analytic with cross-sectional approach. The population is FKIK UNJA medical profession students who participated in the OSCE UKMPPD for the period of May 2018 and August 2018 as many as 59 students .The sample is the entire population (total sampling). Student learning approach data obtained by using the questionnaire